The Parallax and 3D Kinematics of Water Masers in the Massive Star-forming Region G034.43+0.24 - Xiaofeng Mai; Bo Zhang; M. J. Reid; L. Moscadelli; Shuangjing Xu; Yan Sun; Jingdong Zhang; Wen Chen; Shiming Wen; Qiuyi Luo; Karl M. Menten; Xingwu Zheng; et al. (The Astrophysical Journal, 2023)
We report a measurement of the trigonometric parallax of 22 GHz water masers in the massive star-forming region G034.43+0.24 as part of the Bar and Spiral Structure Legacy Survey using the Very Long Baseline Array. The parallax is 0.330 ± 0.018 mas, corresponding to a distance of ${3.03}_{-0.16}^{+0.17}$ kpc. This locates G034.43+0.24 near the inner edge of the Sagittarius spiral arm and at one end of a linear distribution of massive young stars that cross nearly the full width of the arm. The measured three-dimensional motion of G034.43+0.24 indicates a near-circular Galactic orbit. The water masers display arc-like distributions, possibly bow shocks, associated with winds from one or more massive young stars.